2014
DOI: 10.1155/2014/687697
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Analgesic Effects of Leonurus cardiaca L. in Mice by Formalin, Tail Flick and Hot Plate Tests

Abstract: Leonurus cardiaca, commonly known as motherwort, is a member of the Lamiaceae family. It has a number of interesting biological activities, for example, sedative and hypotensive, antioxidant, anti-inflammatory, and antimicrobial activities. The aim of the present study was to investigate the effect of alcoholic extract of aerial part of Leonurus cardiaca on nociceptive response using formalin, tail flick, and hot plate tests in mice. The acute treatment of mice with an ethanolic extract at doses of 500 and 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
0
25
0
2
Order By: Relevance
“…The tail-flick test investigates a spinal reaction which measures nociceptive response latencies to thermal stimuli and determines the central analgesic effects of drugs [38,39]. The present study has demonstrated that sodium diclofenac and three doses of PPE alleviated the pain over 60 min to thermal stimuli.…”
Section: Discussionmentioning
confidence: 51%
“…The tail-flick test investigates a spinal reaction which measures nociceptive response latencies to thermal stimuli and determines the central analgesic effects of drugs [38,39]. The present study has demonstrated that sodium diclofenac and three doses of PPE alleviated the pain over 60 min to thermal stimuli.…”
Section: Discussionmentioning
confidence: 51%
“…Following the antinociceptive studies, MECN attenuated the chemical-induced (i.e., acetic acid- and formalin-induced) and thermal-induced (i.e., hot plate model) nociceptive models suggesting that the antinociceptive profile of MECN includes peripheral and central mechanisms of action. This suggestion was based on previous claims that any substances that can attenuate the abdominal constriction and hot plate tests [ 40 ] or reversed the response latency to formalin-induced nociception in both the early and late phases of formalin test [ 41 ] possess peripheral and central antinociceptive activity.…”
Section: Discussionmentioning
confidence: 99%
“…The hot plate test is aimed at studying the spinal antinociceptive potential of any tested substances by measuring the animal nociceptive response latencies to thermal stimulus following treatment with the substances. The principal response of thermal-induced nociception occurs predominantly at the supraspinal level [ 41 ]. The hot plate test is specifically used to investigate the central antinociceptive potential of any extract/compound and is specifically affected only by the centrally acting drugs (i.e., opioids) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formalin test is a standard test for measuring pain response and is determined by the sum of time (in seconds) that the animal scratches, licks, or bites the formalin injection site. The times are measured every 5 minutes, and the numerical value represents the amount of pain (12,13). After placing the animal on a glass plate, 2% formalin at a volume of 50 μL was injected into the right submucosal tissue of the upper lip, lateral to the nose using a 26 gauge needle.…”
Section: Formalin Testmentioning
confidence: 99%